A Phase II feasibility study of oral etoposide given concurrently with radiotherapy followed by dose intensive adjuvant chemotherapy for children with newly diagnosed high‐risk medulloblastoma (protocol POG 9631): A report from the Children's Oncology Group. Issue 6 (21st December 2016) - Esbenshade, Adam J.; Kocak, Mehmet; Hershon, Linda; Rousseau, Pierre; Decarie, Jean‐Claude; Shaw, Susan; Burger, Peter; Friedman, Henry S.; Gajjar, Amar; Moghrabi, Albert
Abstract: Background: Children with high‐risk medulloblastoma historically have had a poor prognosis. The Children's Oncology Group completed a Phase II study using oral etoposide given with radiotherapy followed by intensive chemotherapy. Procedure: Patients enrolled in the study had high‐risk disease defined as ≥1.5 cm 2 of residual disease postsurgery or definite evidence of central nervous metastasis. All patients underwent surgery followed by radiotherapy. During radiation, the patients received oral etoposide (21 days on, 7 off) at an initial dose of 50 mg/m 2 per day (treatment 1), which was reduced to 35 mg/m 2 per day (treatment 2) due to toxicity. After radiotherapy, the patients received chemotherapy with three cycles of cisplatin and oral etoposide, followed by eight courses of cyclophosphamide and vincristine. Results: Between November 1998 and October 2002, 53 patients were accrued; 15 received treatment 1 and 38 treatment 2. Forty‐seven patients (89%) were eligible. Response to radiation was excellent, with 19 (40.4%) showing complete response, 24 (51.1%) partial response, and four (8.5%) no recorded response. The overall 2‐ and 5‐year progression‐free survival (PFS) was 76.6 ± 6% and 70.2 ± 7%, respectively. The 2‐ and 5‐year overall survival (OS) was 80.9 ± 6% and 76.6 ± 6%, respectively. Clinical response postradiation and PFS/OS were not significantly different between the treatment groups. There was a trend toward a difference in 5‐year PFS between those without and with metastatic disease ( P = 0.072). Conclusions: Oral etoposide was tolerable at 35 mg/m 2 (21 days on and 7 days off) when given during full‐dose irradiation in patients with high‐risk medulloblastoma with encouraging survival data.